Efektivitas video edukasi terhadap perilaku personal hygiene santriwati - Febrianty, Yayuk; Arwan, Arwan; Herman, Achmad; Fadjriah, Rasyika Nurul; Wahyuni, Rosa Dwi (Holistik Jurnal Kesehatan, 2026)
Background: Personal hygiene is an essential component of the clean and healthy living behavior. program in islamic boarding schools. High-density living conditions, shared activities, and communal habits increase the risk of disease transmission among students. Educational videos serve as an effective medium for health promotion because they deliver messages visually and are easy to understand. Purpose: To determine the effectiveness of educational video media in improving personal hygiene behavior among female students at an Islamic boarding school. Method: A quasi-experimental study with a one-group pretest-posttest design was conducted to measure the impact of an educational video intervention based on the five stages of the transtheoretical model (precontemplation, contemplation, preparation, action, and maintenance). The intervention was delivered in five video sessions according to the stages of behavior change. This study was conducted at the Al-Istiqamah Modern Islamic Boarding School in Ngatabaru, Sigi Regency, from August to November 2025. Results: There were no negative ranks in pretest and posttest scores at all stages of behavior change, indicating that all participants experienced improved personal hygiene behavior after the intervention. A Wilcoxon test for all variables showed a p-value of 0.001 < α = 0.05, indicating a significant change after the educational video. Conclusion: Educational video media is effective in improving personal hygiene behavior among female students at all stages of behavior change.   Keywords: Clean and Healthy Living Behavior; Educational Videos; Female Islamic Students; Personal Hygiene.   Pendahuluan: Personal hygiene merupakan bagian penting dari penerapan Perilaku Hidup Bersih dan Sehat (PHBS) di pesantren. Kepadatan hunian, aktivitas bersama, dan kebiasaan hidup komunal meningkatkan risiko penularan penyakit di kalangan santri. Media video edukasi dapat menjadi metode edukasi efektif karena mampu menyampaikan pesan kesehatan secara visual dan mudah dipahami. Tujuan: Untuk mengetahui efektivitas media video edukasi terhadap perubahan perilaku personal hygiene pada santriwati. Metode: Quasi eksperimental dengan desain one group pretest –posttest untuk mengukur dampak intervensi video edukasi berdasarkan lima tahap transtheoretical model (prakontemplasi, kontemplasi, persiapan, aksi, pemeliharaan). Intervensi diberikan dalam 5 sesi video sesuai tahapan perubahan perilaku. Penelitian ini dilaksanakan di Pondok Pesantren Modern Al-Istiqamah Ngatabaru, Kabupaten Sigi, pada bulan Agustus-November tahun 2025. Hasil: Peningkatan nilai pretest dan posttest pada seluruh tahap perubahan perilaku tidak ditemukan negative ranks, sehingga seluruh partisipan mengalami peningkatan perilaku personal hygiene setelah intervensi. Uji Wilcoxon pada seluruh variabel menunjukkan nilai p = 0.001 < α = 0.05 yang berarti terdapat perubahan signifikan setelah pemberian video edukasi. Simpulan: Media video edukasi efektif dalam meningkatkan perilaku personal hygiene santriwati pada seluruh tahap perubahan perilaku   Kata Kunci: Perilaku Hidup Bersih Dan Sehat (PHBS); Personal Hygiene; Santriwati; Video Edukasi.